Traces of Souffles: on cultural production in contemporary Morocco. Issue 3 (1st December 2020) - Esposito, Claudia
Abstract : This article examines contemporary cultural production in Morocco and focuses in particular on how poet-artist Abdellatif Laâbi, founder of the journal Souffles, and writer-artist Mahi Binebine display ties of filiation. Bringing to light the artistic and social collaborations that these two cultural actors nurture in Morocco, the article traces a filial genealogy between Laâbi and Binebine and examines the post-independence years to reveal the spirit of combat that lies at the origin of the current artistic scene in Morocco. Questioning the link between art and the public, the article concludes by acknowledging the tension between art and market-driven concerns inherent in an increasingly competitive art business.